2020
DOI: 10.1136/rmdopen-2020-001202
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and residential clustering at disease onset of anti-MDA5-associated interstitial lung disease

Abstract: ObjectivesTo investigate whether the onset of polymyositis (PM)/dermatomyositis (DM)-associated interstitial lung disease (ILD) is influenced by season and residence in the context of myositis-specific autoantibodies.MethodsFor patients with PM/DM-associated ILD enrolled in a multicentre cohort, 365 and 481 patients were eligible for seasonal and geographical analysis, respectively, based on the availability of reliable clinical information. The patients were divided into three groups: (1) anti-melanoma differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 26 publications
2
30
0
Order By: Relevance
“…A detailed epidemiologic study from Japan revealed that cases of anti-MDA5 DM were clustered in the rural areas around the Kiso river with a link to detection of Coxsackie virus in the water with a seasonality from October to March [36,37]. Similar case clustering has been reported around the Yangtze river in the Jiangsu province in China.…”
Section: Environmentalsupporting
confidence: 52%
“…A detailed epidemiologic study from Japan revealed that cases of anti-MDA5 DM were clustered in the rural areas around the Kiso river with a link to detection of Coxsackie virus in the water with a seasonality from October to March [36,37]. Similar case clustering has been reported around the Yangtze river in the Jiangsu province in China.…”
Section: Environmentalsupporting
confidence: 52%
“…It is also interesting to note that a geographical distribution of the disease has also been reported in Japan, with an increased prevalence of anti-MDA5 DM in patients living in rural areas as opposed to urban areas as well as in patients residing near freshwater ( 103 , 104 ).…”
Section: Pathogenesis Of the Diseasementioning
confidence: 75%
“…The hypothesis of a viral trigger of anti-MDA5 DM is suggested by epidemiological studies that highlighted a seasonal distribution of the disease. Classically, anti-MDA5 DM onset follows a seasonal repartition with an epidemic period in fall and winter, a peak in late winter and spring and a dip in summer, following respiratory virus epidemic period ( 102 , 103 ). In the hypothesis of a viral infection as a possible initiator of autoimmunity, the scenario could involve an activation of MDA5 in the infected cells, leading to IFN-I production and increased levels of MDA5, followed by an excessive local apoptosis favored by a specific genetic background (intronic variant of WDFY4).…”
Section: Pathogenesis Of the Diseasementioning
confidence: 99%
“…In genetically susceptible individuals, viral, bacterial, and parasitic infections have been suspected to induce autoimmunity and even exacerbate existing autoimmune conditions (129). Epidemiological data shows that subsets of polymyositis (PM) and DM patients defined by various myositis-specific antibodies tend to develop disease at specific times of the year (82,130). This seasonal clustering of disease onset could be indicative of a common environmental trigger such as infection (82).…”
Section: Dm and Infectionsmentioning
confidence: 99%